COMPUTER CALCULATIONS OF THE DYNAMICS OF THE SLAG ENTRAPPING IN GATING SYSTEM ON THE BASIS OF THE NAVJE-STOCKS EQUATIONS - F. S. Lukashevich; S. G. Lihouzov; O. I. Chichko (Литьë и металлургия)
On the basis of equations of Navje-Stocks t h e ^ mathematical model for calculation of trajectory of the moving in gating system non-metallic particle, which takes into account the three-dimensional character of speed field and Archimedes power. The proportion of particles, passing through the gating system in casting, is calculated by the example of different variants of gating systems by the mathematical model.